Coupled Coincidence Points of Mappings in Ordered Partial Metric Spaces. (20th March 2012) - Golubović, Zorana; Kadelburg, Zoran; Radenović, Stojan
Abstract : New coupled coincidence point and coupled fixed point results in ordered partial metric spaces under the contractive conditions of Geraghty, Rakotch, and Branciari types are obtained. Examples show that these results are distinct from the known ones.